Honest signaling and the double counting of inclusive fitness. Issue 5 (4th September 2019) - Levin, Samuel R.; Caro, Shana M.; Griffin, Ashleigh S.; West, Stuart A.
Abstract: Inclusive fitness requires a careful accounting of all the fitness effects of a particular behavior. Verbal arguments can potentially exaggerate the inclusive fitness consequences of a behavior by including the fitness of relatives that was not caused by that behavior, leading to error. We show how this "double‐counting" error can arise, with a recent example from the signaling literature. In particular, we examine the recent debate over whether parental divorce increases parent–offspring conflict, selecting for less honest signaling. We found that, when all the inclusive fitness consequences are accounted for, parental divorce increases conflict between siblings, in a way that they can select for less honest signaling. This prediction is consistent with the empirical data. More generally, our results illustrate how verbal arguments can be misleading, emphasizing the advantage of formal mathematical models.